First discovery of the Miocene morthen Atlantic sperm whale Orycterocetus in the Mediterranean - BIANUCCI, GIOVANNI; LANDINI, WALTER; VAROLA A. (2004)
An incomplete mandible of a fossil sperm whale (Odontoceti; Physeteridae) is described. It is a portion of elongated and narrow symphysis with cylindrical and slightly curved teeth without enamel. The specimen, collected from the Miocene "Pietra leccese" sediments of South Italy, appears to represent a species of Orycterocetus, and is the first such record from the Mediterranean. Considering the wide diffusion of Orycterocetus in the North Atlantic, we believe its rare presence in the Mediterranean as occasional and due to a certain degree of interchange between the Mediterranean and the North Atlantic cetacean fauna during the Miocene. © 2004 Elsevier SAS. All rights reserved.